2022
DOI: 10.1108/nfs-02-2022-0043
|View full text |Cite
|
Sign up to set email alerts
|

The effects of folic acid supplementation on depression in adults: a systematic review and meta-analysis of randomized controlled trials

Abstract: Purpose This study aims, a systematic review and meta-analysis, to evaluate the effects of folic acid (folate) on patients with depression. Design/methodology/approach Related articles were found by searching PubMed, SCOPUS, Web of science and Cochrane’s Library, from inception to January 2022. Weighted mean differences (WMD) were pooled using a random-effects model. Heterogeneity, sensitivity analysis and publication bias were reported using standard methods. Findings Pooled analysis of six randomized con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…A collective analysis of six RCTs demonstrated that supplementation of folic acid resulted in a decrease in depression scores, as measured by the Beck Depression Inventory (WMD: −3.9; 95%CI: −5.3, −2.4). Additionally, it resulted in a lower depression score on the Hamilton Depression Inventory (WMD: −3.5; 95%CI: −4.6, −2.4); p < 0.001) compared to the control group [ 51 ]. A meta-analysis consisting of data from 15,315 participants (1769 subjects with depression and 13,546 control subjects) revealed a significant association between folate status and depression (pooled adjusted OR:1.42; 95%CI: 1.1, 1.83) [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…A collective analysis of six RCTs demonstrated that supplementation of folic acid resulted in a decrease in depression scores, as measured by the Beck Depression Inventory (WMD: −3.9; 95%CI: −5.3, −2.4). Additionally, it resulted in a lower depression score on the Hamilton Depression Inventory (WMD: −3.5; 95%CI: −4.6, −2.4); p < 0.001) compared to the control group [ 51 ]. A meta-analysis consisting of data from 15,315 participants (1769 subjects with depression and 13,546 control subjects) revealed a significant association between folate status and depression (pooled adjusted OR:1.42; 95%CI: 1.1, 1.83) [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…One meta‐analysis reported that vitamin B12 or folate decreased the risk of depression relapse and the onset of symptoms in at‐risk people (Almeida et al, 2015) and two meta‐analyses reported no significant benefit from combined B vitamin supplementation (Markun et al, 2021; Young et al, 2019), or vitamin B12 administered alone (Markun et al, 2021). Analysis of findings from folic acid supplementation trials has reported a benefit in improving depressive symptoms (Altaf et al, 2021; Khalili et al, 2022; Zheng et al, 2020), although the number of studies was small, sample sizes were generally small, a wide range of doses was used and significant heterogeneity was reported across studies. Results from a single RCT suggest that folic acid may be an effective adjunct to fluoxetine for treating depression in women (Venkatasubramanian et al, 2013), but no trials included women with a defined menopausal status.…”
Section: Symptoms Of the Menopausementioning
confidence: 99%
“…Probiotics consist of many types of microbes. The most commonly used microbes as probiotics are species from the genera Lactobacillus, Bifidobacterium, and Saccharomyces ( 16 ). Probiotics must be administered in a live state and in an effective dosage ( 15 ).…”
Section: Health Beneficial Effects Of Probioticsmentioning
confidence: 99%
“…Some studies have found that probiotics can reduce symptoms of depression and improve the condition of patients ( 14 ). Gut probiotics can produce vitamins, such as vitamin B (Folic Acid and Pyridoxine), which, when deficient, may be involved in the etiology of depression and hinder the treatment of depression in patients ( 15 , 16 ). In addition, pyridoxine can also reduce symptoms of depression and anxiety ( 17 ).…”
Section: Introductionmentioning
confidence: 99%